2020
DOI: 10.1101/2020.09.03.281667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptome-Wide Off-Target Effects of Steric-Blocking Oligonucleotides

Abstract: Steric-blocking oligonucleotides (SBOs) are short, single-stranded nucleic acids designed to modulate gene expression by binding to mRNA and blocking access from cellular machinery such as splicing factors. SBOs have the potential to bind to near-complementary sites in the transcriptome, causing off-target effects. In this study, we used RNA-seq to evaluate the off-target differential splicing events of 81 SBOs and differential expression events of 46 SBOs. Our results suggest that differential splicing events… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This review has summarized the potential contributions of innate immune system activation and microbial dysbiosis to HS pathogenesis. While studies utilizing single cell omics approaches have already revealed insight into HS pathology and deregulation of host responses (189)(190)(191) advancements in spatial transcriptomics and proteomics should be utilized to further understanding of deregulated innate immunity at the host-pathogen interphase. Future longitudinal studies simultaneously evaluating the focal genetic makeup, innate immunity, microbial dysbiosis and bacterial biofilms will provide detailed insights in HS pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…This review has summarized the potential contributions of innate immune system activation and microbial dysbiosis to HS pathogenesis. While studies utilizing single cell omics approaches have already revealed insight into HS pathology and deregulation of host responses (189)(190)(191) advancements in spatial transcriptomics and proteomics should be utilized to further understanding of deregulated innate immunity at the host-pathogen interphase. Future longitudinal studies simultaneously evaluating the focal genetic makeup, innate immunity, microbial dysbiosis and bacterial biofilms will provide detailed insights in HS pathogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Omicron can enter cells effectively through the endosomal pathway independent of TMPRSS2 and is weak in inducing syncytial formation. 33,[35][36][37][38][39] Variants preceding Omicron tended to adopt the TMPRSS2-mediated membrane fusion route to infect host cells, but only a low proportion of upper respiratory tract cells expressed both ACE2 and TMPRSS2. This explains why Omicron infects the upper respiratory tract more frequently than its predecessors.…”
Section: The Severity Of the Disease Caused By Omicron Infectionmentioning
confidence: 99%
“…50 The proximity of H655Y, N679K, P681H, and D796Y to the furin cleavage site in the spike protein has been hypothesized to be associated with increased infectivity 51 ; however, cellular-level experiments have demonstrated these mutations may contribute to a weakening in facilitating S1/S2 cleavage. 33,[37][38][39] The NTD contains four mutations, three deletions and one insertions: A67V, del69/70, T95I, G142D, del143/145, N211I, del212, and ins214EPE. Del69/70 also existed in Alpha and can be recognized by a useful detection method called s-gene target failure (SGTF).…”
Section: Mutations In Spike Protein Of Omicronmentioning
confidence: 99%
See 2 more Smart Citations